Ai Produced Inventions And Ipr Policy During Covid-19 - Arora, Nikita (Trinity Law Review, 2021)
The disease has spread to approximately 214 nations and areas, according to the World Health Organisation’s (WHO) official website of Coronavirus. While diseases spread ruthlessly over the world, science and technology are fighting back in equal measure. The pandemic puts nations ’medical capabilities and political will to the test. It also poses several philosophical issues. It is a test of humanity as a whole. Artificial Intelligence (AI) aims to mimic human cognition. It will result in considerable changes in health care, owing to the increasing accessibility of healthcare data and the quick advancement of analytical procedures. During the present COVID-19 pandemic, AI is being utilized to aid and advice doctors in making a diagnosis, assist radiologists in refining image explanation, and help enhance drug development research. There is still a lot of uncertainty in the realm of AI-generated intellectual property (IP) protection. The goal of this research is to determine the impact of international and national laws and treaties on IP rights for AI-generated pandemic solutions.